Control of the lungs via the human brain using neurosurgery. - Hyam, J; Aziz, T; Green, A (2014)
Neurosurgery can alter cardiorespiratory performance via central networks and includes deep brain stimulation (DBS), a routinely employed therapy for movement disorders and chronic pain syndromes. We review the established cardiovascular effects of DBS and the presumed mechanism by which they are produced via the central autonomic network. We then review the respiratory effects of DBS, including modulation of respiratory rate and lung function indices, and the mechanisms via which these may occur. We conclude by highlighting the potential future therapeutic applications of DBS for intractable airway diseases.